Marked clinical heterogeneity in congenital hyperinsulinism due to a novel homozygous ABCC8 mutation. (14th March 2021) - Takasawa, Kei; Miyakawa, Yuichi; Saito, Yoko; Adachi, Eriko; Shidei, Tsunanori; Sutani, Akito; Gau, Maki; Nakagawa, Ryuichi; Taki, Atsuko; Kashimada, Kenichi; Morio, Tomohiro
Abstract: Background: The most severe forms of congenital hyperinsulinism (CHI) are caused by inactivating mutations of two KATP channel genes, KCNJ11 and ABCC8 . Unresponsiveness to diazoxide and need for subtotal pancreatectomy can usually be predicted by genetic form, particularly biallelic mutations in KATP channel genes. A few reports indicated marked clinical heterogeneity in siblings with identical biallelic mutations in ABCC8 . The clinical heterogeneity in biallelic KATP CHI was speculated to be caused by epigenetic and environmental factors or related to differences in splicing factor machinery. Objective: To elucidate the clinical pathophysiology, especially heterogeneity, among three cases with CHI caused by a homogenous novel mutation. Patients and Methods: We report a case series that includes two siblings and one unrelated individual with CHI caused by a homogenous 1‐bp deletion around the splice acceptor site at the exon 35 mutation of ABCC8, which exhibited markedly distinct phenotypes. To assess the effect of the mutation on splicing, we performed digital droplet polymerase chain reaction (ddPCR) on normal pancreas tissue and a patient's lymphocytes. Results: ddPCR of ABCC8 cDNA revealed that expression of exon 35 and its upstream and downstream regions did not differ. These data suggested that clinical heterogeneity may not be caused by differences in splicing factor machinery. Conclusion: The phenotypic variation in homozygotes could not be explained by splicing abnormalities. Though early genetic diagnosis of KATP CHI could contribute to selecting appropriate therapeutic options, more deliberate selection of therapeutic options in diffuse CHI due to biallelic ABCC8 mutations may be required.